OPTIMALISASI PELATIHAN DIGITAL MARKETING PADA USAHA KULINER DI KAWASAN BRAGA, KOTA BANDUNG - Kristinae, Vivy; Ferdinand, Ferdinand (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to optimize the ability of culinary business actors in the Braga area, Bandung City, in utilizing digital marketing as a strategy to increase business competitiveness. The main problems faced by partners include low digital literacy, limited strategic use of social media, and not optimal use of marketplaces and digital promotional content. The implementation method uses a participatory approach through training, mentoring, direct practice, as well as monitoring and evaluation. Activity partners are micro and small-scale culinary business actors in the Braga area. The results of the activity show that there is an increase in business actors' understanding of the concept of digital marketing, an improvement in the quality of promotional content, the use of social media in a more structured manner, and an increase in the reach of online marketing. This activity proves that targeted and applicable digital marketing training is able to increase the marketing capacity of culinary businesses and support business sustainability in the digital economy era.